Applications of hydrogen peroxide and derivatives - Jones, Craig W. (Royal Society of Chemistry, 1999)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. "Simple, but beautifully versatile". Perhaps not a description many would choose for hydrogen peroxide, but an accurate one none the less, and this unique book explains the reasons behind the description. Beginning with an historical overview, and guidelines for the safe handling of peroxygens, Applications of Hydrogen Peroxide and Derivatives goes on to cover key activation mechanisms, organic functional group oxidations and the use of hydrogen peroxide with heterogeneous catalysts. The clean-up of environmental pollutants; chemical purification; and extraction of metals from their ores are also discussed in detail, using actual examples from industry. The versatility of this reagent may well prove to be a key to integrated pollution control in the future. This book should therefore be read by academics and industrialists at all levels, to encourage wider applications of the use of hydrogen peroxide in laboratories
Keywords: Hydrogen peroxide.; elektronické knihy; electronic books